THE EFFECT OF TEMPERATURE ON THE PERFORMANCE OF ACTIVATED CARBON OVER CATALYTIC CRACKING OF CRUDE PALM OIL - Nazarudin Nazarudin; Ulyarti Ulyarti; Oky Alfernando; Ira Galih; Susilawati Susilawati; Aris Doyan (Jurnal Penelitian Pendidikan IPA, 2019)
This research was carried out to investigate the effect of temperature in carbon production on its performance in the catalystic cracking of CPO to fuel.  The carbon was produced using palm shell at 2 different temperatures (450 and 550oC).  The cracking of CPO was carried out with and without the active carbon catalyst.  The result showed that the use of catalyst increase the conversion of both gas and liquid conversion.  The use of higher temperature in the production of active carbon catalyst increased the performance of the catalyst, in particular, for the liquid conversion. Keywords :Activated carbon, catalyst, catalytic cracking, crude palm oil